Muscle mass at the time of diagnosis of nonmetastatic colon cancer and early discontinuation of chemotherapy, delays, and dose reductions on adjuvant FOLFOX: The C‐SCANS study. Issue 24 (7th September 2017) - Cespedes Feliciano, Elizabeth M.; Lee, Valerie S.; Prado, Carla M.; Meyerhardt, Jeffrey A.; Alexeeff, Stacey; Kroenke, Candyce H.; Xiao, Jingjie; Castillo, Adrienne L.; Caan, Bette J.
Abstract : BACKGROUND: For many chemotherapy regimens dosed based on body surface area (BSA), patients experience dose reductions or delays or discontinue treatment, thereby reducing survival. Consideration of body composition may be useful in individualizing chemotherapy dosing, but to the authors' knowledge few studies to date have examined the association of body composition with chemotherapy tolerance in patients with colon cancer. METHODS: The authors identified patients with nonmetastatic colon cancer who were diagnosed from 2006 through 2011 at Kaiser Permanente and who received leucovorin calcium/calcium folinate, 5‐fluorouracil, and oxaliplatin (FOLFOX) as initial adjuvant chemotherapy (533 patients). Patients' muscle mass was quantified using clinically acquired computed tomography scans. The authors quantified chemotherapy doses, treatment dates, and related toxicities using the electronic medical record. In logistic regression models adjusting for age, sex, and American Joint Committee on Cancer stage of disease, the authors examined associations of muscle tertiles with early treatment discontinuation (<6 cycles), treatment delay (>3 days off schedule for ≥3 times), and/or dose reduction (relative dose intensity ≤ 0.70, based on planned treatment). RESULTS: The average age of the patients at the time of diagnosis was 58.7 years; BSA was 1.9 m 2 and body mass index was 28.7 kg/m 2 . Compared with the highest sex‐specific tertile of muscle mass, patients in the lowest tertile were more likely to experience toxicities and had twice the risk of adverse outcomes while receiving FOLFOX; for early discontinuation, the odds ratio (OR) was 2.34 (95% confidence interval [95% CI], 1.04‐5.24; P for trend = .03), whereas the ORs were 2.24 (95% CI, 1.37‐3.66; P for trend = .002) for treatment delay and 2.28 (95% CI, 1.19‐4.36; P for trend = .01) for dose reduction. CONCLUSIONS: Lower muscle mass is associated with greater toxicity and poor chemotherapy adherence among patients receiving FOLFOX. Many chemotherapy drugs are dosed based on BSA, but treatment may be better individualized if muscle mass is considered. Cancer 2017;123:4868‐77 . © 2017 American Cancer Society . Abstract : In what to their knowledge is the largest study to date to examine whether muscle mass influences chemotherapy outcomes, the authors find that patients with nonmetastatic colon cancer with low muscle mass at the time of diagnosis are at high risk of dose delays, reductions, and discontinuation while receiving adjuvant leucovorin calcium/calcium folinate, 5‐fluorouracil, and oxaliplatin (FOLFOX). Further studies are needed to determine whether information regarding body composition derived from diagnostic computed tomography scans could optimize chemotherapy dosing and/or help target interventions to help maintain muscle mass during chemotherapy.